If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 6x + -7) + -162 = 9(4x + 5) Reorder the terms: 3(-7 + x + 6x) + -162 = 9(4x + 5) Combine like terms: x + 6x = 7x 3(-7 + 7x) + -162 = 9(4x + 5) (-7 * 3 + 7x * 3) + -162 = 9(4x + 5) (-21 + 21x) + -162 = 9(4x + 5) Reorder the terms: -21 + -162 + 21x = 9(4x + 5) Combine like terms: -21 + -162 = -183 -183 + 21x = 9(4x + 5) Reorder the terms: -183 + 21x = 9(5 + 4x) -183 + 21x = (5 * 9 + 4x * 9) -183 + 21x = (45 + 36x) Solving -183 + 21x = 45 + 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. -183 + 21x + -36x = 45 + 36x + -36x Combine like terms: 21x + -36x = -15x -183 + -15x = 45 + 36x + -36x Combine like terms: 36x + -36x = 0 -183 + -15x = 45 + 0 -183 + -15x = 45 Add '183' to each side of the equation. -183 + 183 + -15x = 45 + 183 Combine like terms: -183 + 183 = 0 0 + -15x = 45 + 183 -15x = 45 + 183 Combine like terms: 45 + 183 = 228 -15x = 228 Divide each side by '-15'. x = -15.2 Simplifying x = -15.2
| 2(x+1)=2x+5 | | 4w^3-20w^2=56w | | -4y-4+3y+6=1 | | 4(x-1)-(x+2)=12 | | 10x+7=10+9x | | 4x+2y=86400 | | 5*-30=15 | | v^2-5v+11=(v-2)(v-6) | | -3x^2-10x-8=0 | | 6x+28=16x-82 | | 3(2x+8)=8x+24-2x | | 3(2x+8)=8x-7 | | 4(x+9)+x(x-1)=x(6+x) | | 3(2x+8)=6x-7 | | 4x+26=64-14x | | 4x+26=64-10x | | x+7(x-5)=2(5-x) | | b^2-10b+25=0 | | (x-3)(x+4)=x*x+4 | | 8+2(x+3)=10 | | 6x^2-18x+12=0 | | b^2-10b+2=0 | | 4(8-s)+6=-2 | | 6(4x-1)=7(15+3x) | | 3x-8=4(5-3x)+9 | | 6x^2-72x+18=0 | | 1x+6x-7-54=12x+5 | | 5(x+2)=2(x-13) | | 65-7x=38x+15 | | 5x-6(4+5x)=-6 | | x^3-18x^2+17x=0 | | 5-9x=49-37x |